Caractérisation chimique des huiles essentielles de Pistacia lentiscus L. Evaluation du pouvoir antimicrobien - Bengeunouna, Linda; Belkabdji, Zahira (My University, 2019)
This work focused on the valuation of a plant species Pistacia lentiscus L, growing in the wild and harvested in the region of Mostaganem, by evaluating certain biological properties of the essential oil such as antimicrobial activity. The extraction of the essential oil from the fresh leaves and twigs of the lentiscus was carried out by the hydrodistillation method (Clevenger type) and which gave a yield of 0.42%. The study of the antimicrobial activity by aromatogram showed a good inhibitory effect of Pistacia lentiscus oil on the six reference strains tested, satisfactory values of diameter of zones of inhibition (16.71, 20.07, 12, 19, 19.56 and 23 mm) and MIC values (0.625, 0.625, 0.25, 0.25 and 0.125%) for bacteria: Pseudomonas aeruginosa, Acinetobacter baumannii, Proteus mirabilis, Staphylococcus aureus, Bacillus cereus, Salmonella enterica respectively.
Keywords: Pistacia lentiscus L., essential oil, chemical characterization, antimicrobial activity.